Desenvolvimento farmacotécnico e validação analítica de comprimidos revestidos a partir do extrato padronizado de Actaea racemosa L. - Bagatela, Bianca Souza [UNIFESP] (2017)
The project aims to develop an herbal medicine from the dry extract, standardized in 23-epi-26-desoxiactein, from the roots of the plant species Actaea racemosa L. (Ranunculaceae), popularly known as "black cohosh". The tablets were developed from the dry extract of A. racemosa L. and produced by direct compression. Subsequently, they were coated with the appropriate dispersion. Accelerated and longterm stability studies have been performed to define the period of use and validity. Coated tablets, obtained from the dried extract of A. racemosa L., were standardized in 23-epi-26-desoxiactein, and the analytical methodology was validated.